The impact of infectious disease prevention behavior on quality of life: A moderated mediation model - Fei Wang; Pu Ge; Danyang Li; Lin Cai; Xialei Li; Xinying Sun; Yibo Wu (Wiley, 2022)
Abstract Objective To explore the mechanism of infectious disease prevention behavior on quality of life, and to investigate the mediating role of self‐efficacy and the moderating role of family structure. Methods A total of 3015 subjects were selected by multistage stratified cluster sampling. Results Infectious disease prevention behavior had a significant positive predictive effect on the quality of life (β = 0.08, p < 0.001), The self‐efficacy of family members had a partial mediating effect on the relationship between infectious disease prevention behavior and quality of life (β = 0.01, p < 0.001). Compared to nuclear family, conjugal family (β = 0.05, p < 0.001) and single‐parent family (β = 0.04, p < 0.01) could regulate the relationship between infectious disease prevention behavior and the quality of life, stem family (β = −1.53, p < 0.05), conjugal family (β = 1.63, p < 0.05), and collective family (β = −1.37, p < 0.05) could regulate the relationship between infectious disease prevention behavior and self‐efficacy, conjugal family (β = 0.00, p < 0.001) could regulate the relationship between self‐efficacy and quality of life. Conclusion Infectious disease prevention behavior can affect the quality of life through self‐efficacy. Different family structures play a regulatory role in different paths, and a regulatory mediation model is established.